Resectable Pediatric Nonrhabdomyosarcoma Soft Tissue Sarcoma: Which Patients Benefit from Adjuvant Radiation Therapy and How Much?. (15th March 2012) - Million, Lynn; Donaldson, Sarah S.
Abstract : It remains unclear which children and adolescents with resected nonrhabdomyosarcoma soft tissue sarcoma (NRSTS) benefit from radiation therapy, as well as the optimal dose, volume, and timing of radiotherapy when used with primary surgical resection. This paper reviews the sparse literature from clinical trials and retrospective studies of resected pediatric NRSTS to discern local recurrence rates in relationship to the use of radiation therapy.